A comparison of the usefulness of nuclear beta‐catenin in the diagnosis of desmoid‐type fibromatosis among commonly used anti‐beta‐catenin antibodies. Issue 6 (31st March 2021) - Yamada, Yosuke; Hirata, Masahiro; Sakamoto, Akio; Noguchi, Takashi; Ito, Kan; Nishida, Yoshihiro; Matsuda, Shuichi; Haga, Hironori
Abstract : Desmoid‐type fibromatosis (DF) is a locally aggressive but non‐metastatic (myo)fibroblastic neoplasm. A hallmark of the tumor is nuclear positivity for beta‐catenin in immunohistochemistry due mostly to CTNNB1 mutations. However, a recent study has reported that even beta‐catenin 'nuclear‐negative' DFs can harbor CTNNB1 mutations and that the positive ratio of nuclear beta‐catenin in DF is different among antibodies. Here, we reviewed soft tissue lesions for which the possibility of DF was considered and compared the sensitivity and specificity of nuclear beta‐catenin for the diagnosis of DF among commonly used anti‐beta‐catenin antibodies, i.e., clone beta‐catenin 1, 17C2 and 14. We analyzed 26 cases of DF, 28 cases of benign fibroblastic lesions, and 27 cases of other soft tissue tumors. The sensitivity and specificity of nuclear beta‐catenin for the diagnosis of DF were different among antibodies; 54% and 98% in clone beta‐catenin 1, 85% and 84% in 17C2, and 96% and 62% in 14. IHC of LEF1 showed comparable results with IHC of beta‐catenin, with a sensitivity of 88% and specificity of 76%. Additionally, when beta‐catenin 1 was used, DFs showed characteristic dotted cytoplasmic staining, often appearing as rings. Our results might be helpful for making a correct diagnosis of DF.